Co-management of cataract and glaucoma in the era of minimally invasive glaucoma surgery. Issue 1 (January 2018) - Rabin, Richard L.; Rabin, Arnold R.; Zhang, Amy D.; Burney, Edward N.; Rhee, Douglas J.
Abstract : Purpose of review: This review discusses the options available to be used in conjunction with phacoemulsification cataract surgery to control intraocular pressure. We present a strategy for planning which surgery should be performed based on goals of care. Recent findings: New clinical evidence for using the CyPass, Kahook and Xen45 devices has been published recently and is summarized. Summary: Cataract and glaucoma frequently exist together. Because the field of glaucoma surgical care is expanding and cataract surgery is becoming progressively safer, it is important to frequently re-evaluate our treatment paradigms. We review and evaluate current studies and treatment options.